2017
DOI: 10.1111/pbi.12717
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Populus trichocarpa CYP85A3 promotes growth and biomass production in transgenic trees

Abstract: SummaryBrassinosteroids (BRs) are essential hormones that play crucial roles in plant growth, reproduction and response to abiotic and biotic stress. In Arabidopsis, AtCYP85A2 works as a bifunctional cytochrome P450 monooxygenase to catalyse the conversion of castasterone to brassinolide, a final rate‐limiting step in the BR‐biosynthetic pathway. Here, we report the functional characterizations of PtCYP85A3, one of the three AtCYP85A2 homologous genes from Populus trichocarpa. PtCYP85A3 shares the highest simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 76 publications
11
45
1
Order By: Relevance
“…2). Hence, our results indicated that PtoDET2 could significantly increase BRs level for much enhanced plant growth and biomass yield, consistent with the previous findings that BRs-related genes could promote plant growth [31][32][33][34][35][36][37][38][39][40].…”
Section: Ptodet2 Overexpression Improved Plant Growth and Biomass Yiesupporting
confidence: 92%
See 2 more Smart Citations
“…2). Hence, our results indicated that PtoDET2 could significantly increase BRs level for much enhanced plant growth and biomass yield, consistent with the previous findings that BRs-related genes could promote plant growth [31][32][33][34][35][36][37][38][39][40].…”
Section: Ptodet2 Overexpression Improved Plant Growth and Biomass Yiesupporting
confidence: 92%
“…BRs are the plant-specific steroid hormones that dynamically regulate plant growth and development [30][31][32][33][34][35][36]. In this study, we observed a fast growth and development with more internodes and larger leaves in the PtoDET2-OE transgenic lines ( Fig.…”
Section: Ptodet2 Overexpression Improved Plant Growth and Biomass Yiesupporting
confidence: 52%
See 1 more Smart Citation
“…Every transgenic line was verified by PCR, RT‐qPCR and histochemical staining with β‐glucuronidase (GUS) (Figure S2). In the literature, these three methods are usually used to verify transgenic plants (Jin et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Secondary cell walls in the form of wood and fibers are the most abundant, renewable plant products, and there is a high demand for improving wood and fiber production. Overexpression of Populus trichocarpa CYP85A3, encoding a P450 monooxygenase that catalyzes the conversion of castasterone to BL, enhanced xylem formation and wood production in poplar while the composition of cellulose and lignin and cell wall thickness were not affected, making Populus trichocarpa CYP85A3 a good target for engineering fast-growing woods (Jin et al, 2017). BR signaling also regulates cotton (Gossypium hirsutum) fiber development by modifying the expression of DET2 and PAGPDA1.…”
Section: Manipulation Of Brs In Cropsmentioning
confidence: 99%